Вплив бактеризації Anabaena flos-aquae і Pseudomonas putida та обробки саліциловою кислотою на холодостійкість бобових рослин - Vinnikova, Olha; Drofa, Anna; Raievska, Iryna (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
The paper presents the results of studying the eff ects of exposure of pea (Pisum sativum) and been (Phaseolus vulgaris) seeds or young sprouts to low temperature (4°C) with preliminary treatment of seeds with salicylic acid (SA), or with pure cultures of Anabaena flos-aquae or Pseudomonas putida, or with their mixture. Cold exposure lasting 24 hrs was carried out immediately or 7 days after SA treatment or bacterization of seeds. Morphometric parameters of roots and sprouts, permeability of cell membranes in leaves, activity of polyphenol oxidase and state of actin filaments in root cells were measured. Pea and bean plants differ in cold resistance, and their growth responses to low temperature exposure were multidirectional. Treatment with SА immediately before exposure to cold had a positive effect on cold resistance of pea plants. Under the delayed cold stress, seed bacterization with single bacteria suspensions or their mixture contributed to the development of cold resistance in beans. Bacterization of seeds presumably reduced the permeability of cell membranes in leaves of both plant species and improved the state of actin filaments in root cells. In general, some protective effect for peas was observed due to either bacterial or SА treatment of seeds. In bean plants, the meaningful protective effect occurred after seed bacterization only. Probl Cryobiol Cryomed 2024; 34(2):125–142